Draft Annual Plan 2008-2009 (Sectoral Plans) Volume - I Government of Nagaland - Planning Commission (Planning Commission, 2008)
Traditionally, all the tribes and villages in Nagaland practice shifting cultivation locally known as "Jhum". The Angami and Chakhesang tribes have on the other hand, developed a system of Wet Terraced Rice Cultivation (WTRC), which they practice alongside jhum cultivation. Modem scientific agriculture was introduced only in the 1960's. The impact has not been very appreciable, as most high external input technologies are not suitable for high altitudes and rainfed conditions. Moreover, traditionally Nagas did not cultivate any whiter crop. Only in recent years, non-traditional winter crops such as wheat, barley and some pulses and also oilseeds have been introduced. Now, it is gaining much popularity among the local farmers.
Planning and Co-ordination Department, Government of Nagaland
Planning and Co-ordination Department, Government of Nagaland